Das christliche Leben als ein Weg — Elemente der Wallfahrtstheologie - Maciej Ostrowski (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The Author presents some Biblical texts on symbolic meaning of a way. In theological meaning a way is a symbol of moving forward, developing, growing in the Christian faith, hope, love and wisdom. Progress in the development of sainthood of a person is of a great significance. In this context, the author refers to pilgrimage which is a symbol of the entire Christian life being approaching God. It covers many religious practices, which help to renew the Christian life, develop faith and love.